A systematic review of predictors of international students’ cross-cultural adjustment in China: current knowledge and agenda for future research - Cao, Chun; Meng, Qian (Asia Pacific education review, 2022)
China has emerged as one of the leading destinations for international students, attracting growing research interest in examining their cross-cultural adjustment. Our study moved beyond prior work by offering the first systematic review on predictors of international student adjustment in China, with all its three domains taken into consideration: psychological, sociocultural and academic adjustment. Based on the 33 reviewed articles, a wide range of predictors were identified. Guided by the Job Demands-Resources Model, these predictors were categorized into six broad clusters: demographics, personal resources, contextual resources, personal demands/barriers, contextual demands/resources, and other variables. The reviewed studies placed more emphasis on predictors in resources clusters than on those in demands/barriers clusters. Research strengths, gaps and inconsistencies in the literature were identified and discussed. Accordingly, an agenda was developed to highlight opportunities for theoretical and empirical advancement for future research.